Effect of Preservative Liner Made with Resveratrol-Loaded Pickering Emulsion on the Preservation of Chilled Beef - DU Liying, REN Guoyan, ZHAO Bing, JIANG Haiyuan, CHENG Xiaoyu, XU Chenchen, BAI Jing (Shipin Kexue)
In this study, chitosan (CS) and collagen (COL) composite nanoparticles were used as stabilizer to prepare Pickering emulsion loaded with resveratrol (PE-R). The particle size, potential, rheological properties, antibacterial effect, antioxidant properties and stability (centrifugal stability, storage stability, salt ion stability, pH stability) of PE-R were determined. According to the experimental results, PE60 (with 60% oil phase) was selected as the optimal one and used to prepare a preservative liner, which was placed in the bottom of the tray for the preservation of chilled beef. The results showed that the swelling rate and solubility of the PE60 liner were both significantly reduced, and this liner significantly slowed down the growth rates of thiobarbituric acid reactive substances (TBARS) value and total volatile basic nitrogen (TVB-N) content, inhibited the reproduction of microorganisms, reduced the centrifugal loss, better maintained the color, and extended the shelf life of beef from 6 to 10 days.